2003
DOI: 10.1023/a:1023929630687
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: T-DNA flanking sequences were isolated from 112 Arabidopsis thaliana single-copy T-DNA lines and sequence mapped to the chromosomes. Even though two T-DNA insertions mapped to a heterochromatic domain located in the pericentromeric region of chromosome I, expression of reporter genes was detected in these transgenic lines. T-DNA insertion did not seem to be biased toward any of Arabidopsis' five chromosomes. The observed distribution of T-DNA copies in intergenic sequence versus gene sequence (i.e. 5'-upstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…Castle et al (1993) observed rearrangements in 7 out of 41 TDNA-tagged mutants. Forsbach et al (2003) observed translocations in only 2.6% of 112 single-copy T-DNA lines, but chromosomal rearrangements were more frequent in plant lines with more than one T-DNA insertion. Nacry et al (1998) characterized a reciprocal translocation involving chromosome II and III.…”
Section: Discussionmentioning
confidence: 94%
“…Castle et al (1993) observed rearrangements in 7 out of 41 TDNA-tagged mutants. Forsbach et al (2003) observed translocations in only 2.6% of 112 single-copy T-DNA lines, but chromosomal rearrangements were more frequent in plant lines with more than one T-DNA insertion. Nacry et al (1998) characterized a reciprocal translocation involving chromosome II and III.…”
Section: Discussionmentioning
confidence: 94%
“…To isolate one albino mutant with a 95% probability out of 5,500 transformants from the approximately 35-Mb genome of A. aculeatus , it was calculated that the T-DNA must disrupt gene the function in a 19-kb region around the T-DNA integration locus (Krysan et al 1999). The 1,002-bp deletion at the AapksP locus in the alb1 mutant was relatively larger than those reported for M. oryzae and Arabidopsis , in which the majority of deletions ranged from 1 to 35 bp and 11 to 100 bp, respectively (Brunaud et al 2002; Choi et al 2007; Forsbach et al 2003). Furthermore, the coding region of AapksP is relatively large at 6,645 bp; however, it is not large enough to increase the probability of isolating two albino mutants from 11,000 transformants.…”
Section: Discussionmentioning
confidence: 54%
“…However, also, in that case, the number of additional nucleotides that has been introduced is limited to three base pairs from the left T-DNA border and 21 base pairs from the right T-DNA border. In fact, in many cases, the number of base pairs introduced is even lower, with fewer or no T-DNA sequences introduced from the right border, and sometimes also the base pairs from the left T-DNA border are missing [29]. In practice it is often possible to select cisgenic events that contain no T-DNA sequences, resulting in a plant that only differs from the conventional plant in its location of the cisgene.…”
Section: What If Cisgenic Lbr Potatoes Are Considered a Gmo?mentioning
confidence: 99%